Turnover Intention Analysis In PMA Bogor - Kasmir Kasmir; Jakfar Jakfar; Parwoto Parwoto (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The superiority of a company really depends on the human resources (HR) it has. Excellence in the field of human resources means that the company can retain, nurture and develop its quality employees from time to time in accordance with the standards they have set. Superior employees are those who have advantages compared to employees in other companies, for example abilities and behavior, so that they are able to achieve targets and even exceed what was previously set as their workload.The management of a company that has superior employees must be good at looking after, nurturing and retaining employees so that they continue to perform well and continue to survive in the company. Maintenance can be done by making employees feel happy and at home working in the company. Then by continuing to develop the competencies and talents they have, so that they have the ability, behavior and high loyalty to the company. If this is not done, it will certainly be a problem for employees to maintain and retain their employees.